A retrospective study on parapneumonic effusion in 130 dogs with a clinical diagnosis of pneumonia - Burnotte, Priscilla; Graziano, Nicolas; Gommeren, Kris (Frontiers in Veterinary Science, 2023)
Objective To screen the occurrence of parapneumonic effusion in dogs. Methods Medical records were searched for dogs with a presumptive diagnosis of bacterial pneumonia from 2017 to 2021 at the Liege university teaching hospital. Bacterial pneumonia was presumptively diagnosed based on compatible clinical signs and findings; thoracic radiographs compatible with bacterial bronchopneumonia; and either increased serum C-reactive protein (CRP) levels, a positive bronchoalveolar lavage culture or a positive clinical evolution in response to antibiotic therapy. Patients diagnosed with parasitic or other non-bacterial inflammatory pneumonia or with pulmonary neoplasia were excluded. Signalment, clinical findings, and outcome were recorded. Results One hundred and thirty dogs were included in the study, of which 44 dogs (33.8%) developed a parapneumonic effusion. Four of these dogs (4/44; 9%) had thoracocentesis performed, displaying a modified transudate (2) or septic exudate (2). Conclusions Although parapneumonic effusion in dogs with a presumptive diagnosis of bacterial pneumonia appears to be rather common (33.8%), thoracocentesis or chest tube placement was rarely performed. Furthermore, the outcome of dogs with and without parapneumonic effusion appears to be similar.